2020
DOI: 10.21203/rs.2.20974/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A member of wheat class III peroxidase gene family, TaPRX-2A, enhanced the tolerance of salt stress

Abstract: Background: Salt and drought are the main abiotic stresses that restrict yield of crops. It is reported that peroxidases (PRXs) are involved in various abiotic stress responses. However, few wheat PRXs are characterized in the mechanism of abiotic stresses. Results: In this study, a novel wheat peroxidase (PRX) gene named TaPRX-2A, a member of wheat class III peroxidase gene family, was cloned and characterized in salt stress response. Based on the identification and evolutionary analysis of class III PRXs in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Overexpression of the wild soybean (Glycine soja) GsPRX9 gene was associated with improved salt tolerance in soybean (Glycine max) (Jin et al, 2019). Overexpressing TaPRX-2A in wheat (Triticum aestivum) also increased the tolerance of transgenic lines to salt stress (Su et al, 2020). However, the biological functions and regulatory mechanisms of most CIII PRXs remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of the wild soybean (Glycine soja) GsPRX9 gene was associated with improved salt tolerance in soybean (Glycine max) (Jin et al, 2019). Overexpressing TaPRX-2A in wheat (Triticum aestivum) also increased the tolerance of transgenic lines to salt stress (Su et al, 2020). However, the biological functions and regulatory mechanisms of most CIII PRXs remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Class III PRX genes encode heme-containing enzymes that accept electrons from various donors to catalyze H 2 O 2 metabolism, thus reducing H 2 O 2 concentrations inside plant tissues (Almagro et al, 2009). Class III PRXs are important in protecting against ROS and enhance stress tolerance in plants exposed to salt (Llorente et al, 2002;Kumar et al, 2012;Jin et al, 2019;Su et al, 2020), drought (Llorente et al, 2002;Kumar et al, 2012), cold (Kim et al, 2012) and heat (Requesens et al, 2014) stresses. However, the biological functions and regulatory mechanisms of most CIII PRX genes remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, tolerant species possess a number of ROS detoxifying proteins, such as CAT, POD and SOD, which protect them from oxidative stress (Azevedo-Neto et al 2006). For example, overexpression of IbBBX24 and IbBBX17 in sweet potato improved tolerance to drought and salt stress via scavenging and detoxi cation of ROS (Zhang et al 2022), while transgenic Triticum aestivum overexpressing TaPRX-2A showed increased tolerance to salt as a result of reduced ROS accumulation (Su et al 2020). In this study, overexpression of OsSKL2 in rice reduced H 2 O 2 accumulation and improved the activities of CAT, POD and SOD, thereby enhancing tolerance to drought and salt stress (Fig.…”
Section: Osskl2 Confers To Drought and Salt Stress Via Ros Scavenging...mentioning
confidence: 55%
“…In terms of antioxidant activity, several genes that code for peroxidases were detected in both Mulai and IR29. The role of peroxidase genes in salinity tolerance in soybean (Jin et al 2019) and wheat (Su et al 2020) has been demonstrated, while the regulation of peroxidase biosynthesis by a zinc finger protein has been shown in rice salinity tolerance (Cui et al 2015). The generation of reactive oxygen species (ROS) as brought about by abiotic stresses such as salinity and its negative effects has been well documented in different crops.…”
Section: Discussionmentioning
confidence: 99%